Early Childhood Instruction and Social Development in Kindergarten Learners: A Qualitative Inquiry - Baclig, Geraldine (Azal Arts and Humanities, 2026)
Early childhood education is widely recognized as a critical foundation for learners’ holistic development, particularly in the formation of social competencies such as cooperation, communication, empathy, self-regulation, and conflict resolution. In kindergarten, these social skills are essential for meaningful classroom participation and sustained learning engagement. Aligned with global and national priorities, including Sustainable Development Goal 4, the Department of Education’s MATATAG agenda, and the recommendations of the Second Congressional Commission on Education (EDCOM II), this qualitative study examined how early childhood instructional practices in kindergarten classrooms support learners’ social development in a rural public-school context in the Philippines. Using a qualitative descriptive design, data were gathered through naturalistic classroom observations, semi-structured interviews with kindergarten teachers, and focus group discussions with parents to triangulate perspectives on learners’ social behaviors. Reflexive thematic analysis was employed to identify patterns across data sources. Findings revealed that predictable classroom routines and explicit teaching strategies played a central role in shaping learners’ social behaviors by promoting emotional security, behavioral readiness, and cooperative participation. Observable social development outcomes included improved cooperation, turn-taking, verbal communication, empathy, and self-regulation, particularly during group activities and guided play. Teachers perceived their instructional practices as directly influencing learners’ social development through consistent modeling, guided practice, and reinforcement. However, the depth and frequency of play-based and interactional activities were moderated by contextual constraints uch as large class sizes, limited instructional time, and diverse learner readiness levels.The study concludes that early childhood instruction functions as a deliberate mechanism for social development rather than a outlying aspect of kindergarten education. The findings underscore the need for sustained support for developmentally appropriate, play-based, and interaction-rich instruction, alongside enabling classroom conditions that strengthen learners’ social foundations and readiness for lifelong learning.